المرافعات الشرعية دراسة مقارنة بالقانون المالديفي - موسى، إبراهيم زكريا (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2007)
This study analyses the concept of civil trial procedures in accordance with the Islamic Jurisprudence with a comparison to the Maldivian civil procedures. The focus of the study is on lawsuits and its related issues. The study examines lawsuits and its meaning in accordance with the terminology of Shari`ah. It explains the criteria to differentiate between a plaintiff and a defendant in a lawsuit in accordance with various opinions of Muslim juristic scholars of different schools of thought with emphasis on the importance of granting the right to defend the claims of the defendants. This study also deals with issues related to trials in absentia and means of summoning the defendant to the court in the light of various schools of thought. In addition, the study assesses the importance of conducting public trials in order to avoid accusation of unfairness in making judgments. The research has adopted the descriptive, inductive, analytical and deductive methodologies to prove the suitability of Islamic civil proceedings to undertake various lawsuits. This study intends to prove whether the procedures administered in the Maldivian court system are in accordance with Islamic basic principle of civil procedures, while exploring the areas of improvement to be made in the system so that it is more systematic and fairer to all the parties.